Halal Practices vs Food Heritage: A Case Study of Keropok Lekor Operators in Terengganu, Malaysia - Wan Nazriah Wan Nawawi; Zatul Iffah Mohd Fuza; Yudhiet Fajar Dewantara; Ika Suryono x Ika Suryono Djunaid; Mohd Syahadat Robbi Abdul Ghani (Information Management and Business Review, 2025)
As global demand for halal food continues to grow, Terengganu’s food heritage must navigate the modern requirement for halal certification, especially for products, such as Keropok Lekor, which are exported beyond local markets. Hence, this study aims to examine the sustainability of halal practices in the context of food heritage, specifically focusing on Keropok Lekor operators in Terengganu, Malaysia. While existing literature has primarily addressed halal certification and supply chain management, there is limited exploration of how traditional foods like Keropok Lekor fit within the broader halal framework and cultural heritage. Therefore, a semi-structured interview was conducted with two Keropok Lekor operators in Terengganu. Hence, the interview process has been recorded, and then the recording has been transcribed using the NVIVO software. The theme has then been identified throughout the transcript. The themes used to analyze the transcript have been food heritage, halal practices, and challenges.  By exploring Keropok Lekor as food heritage, investigating the halal practices among the operators, and understanding the challenges they face in maintaining these practices, the study provides insights into the intersection of cultural preservation and halal compliance. With the increasing global demand for halal-certified products, it is crucial to explore how traditional food producers navigate the delicate balance between heritage and halal standards. This study contributes to the growing body of knowledge about the sustainability of halal practices in the food industry.